2022
DOI: 10.35848/1347-4065/ac7626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amplitude modulated capacitively coupled discharge Ar plasma on kinetic energy and angular distribution function of ions impinging on electrodes: particle-in-cell/Monte Carlo collision model simulation

Abstract: We investigated effects of amplitude modulated (AM) capacitively coupled Ar discharge plasma on the ion energy distribution function (IEDF) and the ion angular distribution function (IADF) incident on electrodes using the particle-in-cell/Monte Carlo collision model. For AM discharge, the electron density and electron temperature and the kinetic energy and angle of ions incident on the ground electrode change periodically with AM frequency, whereas ones for continues wave discharge are almost constant. For AM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…This density fluctuation is not strictly consistent with the phase of the FM waveform but has a delay of about 0.2 FM period (1 µs) between the maximum density and the maximum frequency of 18 MHz. Recently, Abe et al [45]. observed a similar phenomenon in amplitude modulated (AM) driven CCP discharges.…”
Section: Electron Kineticsmentioning
confidence: 71%
“…This density fluctuation is not strictly consistent with the phase of the FM waveform but has a delay of about 0.2 FM period (1 µs) between the maximum density and the maximum frequency of 18 MHz. Recently, Abe et al [45]. observed a similar phenomenon in amplitude modulated (AM) driven CCP discharges.…”
Section: Electron Kineticsmentioning
confidence: 71%
“…We demonstrated that AM discharge method can improve the side step coverage and film quality of SiO2 thin films over pattered substrates fabricated by TEOS-PECVD [14]. Moreover, we investigated effects of AM discharge plasmas on IEDF and IADF incident on electrodes using the particle-in-cell/Monte Carlo collision (PIC-MCC) model [20,21]. These PIC-MCC simulation results clarified that the widths of change in the peak of IEDF and FWHM of IADF are controlled by AM level.…”
Section: Introductionmentioning
confidence: 99%